การประเมินความผิดปกติของโครโมโซมปลาดุกอุยที่รับสัมผัสโลหะหนักในสภาพทดลองเลี้ยงในน้ำและตะกอนดินจากเหมืองแร่ทองคำ: Chromosomal Aberration Assessment of Gunther's Walking Catfish (Clarias macrocephalus) after In Vivo Exposure to Heavy Metals Contaminated in Water and Sediment from Gold Mine Area - Phoonaploy, Uraiwan; Chayjun, Apitchayaporn; Ruchuwararak, Patcharin; Tengjaroenkul, Bundit; Neeratanaphan, Lamyai (Asian Health, Science and Technology Reports, 2017)
การศึกษานี้มีวัตถุประสงค์เพื่อประเมินความผิดปกติของโครโมโซมปลาดุกอุย (Clarias macrocephalus) ในสภาพการทดลองเลี้ยงในน้ำและตะกอนดินจากเหมืองแร่ทองคำ ระยะเวลา 30 วัน เปรียบเทียบกับชุดอ้างอิง วิเคราะห์ปริมาณโลหะหนักในน้ำ ตะกอนดิน และปลาดุกอุยด้วยเครื่อง Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES) เตรียมโครโมโซมจากเนื้อเยื่อไตโดยวิธีทางตรง ผลการศึกษาปริมาณโลหะหนักก่อนการทดลองในน้ำพบปริมาณของสารหนู แคดเมียม โครเมียม และตะกั่ว ในชุดทดลอง มีค่าเฉลี่ย 0.229±0.009 0.007±0.003 0.007±0.000 และ 0.007±0.003 mg/l ตามลำดับ ชุดอ้างอิงตรวจพบค่าเฉลี่ยของสารหนูและตะกั่วเท่ากับ 0.010±0.000 และ 0.010±0.000 mg/l ตามลำดับ แต่ไม่พบแคดเมียมและโครเมียม ซึ่งชุดทดลองมีค่าสารหนูและแคดเมียมเกินค่ามาตรฐาน ปริมาณโลหะหนักในตะกอนดินจากชุดทดลองพบสารหนู แคดเมียม โครเมียมและตะกั่ว มีค่า 130.492±5.570 120.466±14.576 21.031±0.288 และ 36.926±3.265 mg/kg ตามลำดับ ชุดอ้างอิงพบค่าเฉลี่ยของแคดเมียม โครเมียมและตะกั่ว มีค่า 0.390±0.288 11.033±3.074 และ 4.027±1.835 mg/kg ตามลำดับ แต่ไม่พบสารหนู ชุดทดลองมีค่าสารหนูและแคดเมียมเกินค่ามาตรฐานคุณภาพดิน หลังการทดลองเลี้ยงพบว่าปริมาณสารหนู แคดเมียม โครเมียมและตะกั่วในปลาดุกอุยในชุดทดลองมีค่า 0.586±0.404 2.314±2.369 2.090±0.305 และ 0.277±0.011 mg/kg ตามลำดับ ชุดอ้างอิงพบตะกั่วมีค่า 0.162±0.073 mg/kg ในชุดทดลองมีแคดเมียมและโครเมียมเกินค่ามาตรฐานอาหารปนเปื้อน ปลาดุกอุยทั้ง 2 ชุดการทดลองมีโครโมโซมดิพลอยด์ 54 แท่ง (2n = 54) ในชุดทดลองตรวจสอบเซลล์ปลาดุกอุย 3 ตัว ตัวละ 50 เซลล์ พบ 5 รูปแบบความผิดปกติของโครโมโซม คือ single chromatid gap (SCG) deletion (D) fragmentation (F) centric fragmentation (CF) และ isochromatid gap (ISCG) จำนวน 4 9 1 5 และ 2 ตำแหน่ง ตามลำดับ โดยมีจำนวนเซลล์ที่โครโมโซมผิดปกติคิดเป็นร้อยละ 9.33 เซลล์ ลักษณะความผิดปกติที่พบมากที่สุดในตัวอย่างปลาดุกอุย คือ D The objective of this study was to investigate chromosomal aberrations of Gunther's walking catfish (Clarias macrocephalus) exposed to heavy metals contaminated water and sediment from gold mine for 30 days compared to unaffected area. Heavy metal concentrations in water, sediment and C. macrocephalus were measured by using inductively coupled plasma optical emission spectrometry (ICP-OES). Assessment of chromosomal aberration of C. macrocephalus prepared from kidney tissues by direct method. Heavy metal concentrations in water and sediment were analyzed before the experiment. The results showed that the mean value concentrations of arsenic (As), cadmium (Cd), chromium (Cr) and lead (Pb) in water were 0.229±0.009, 0.007±0.003, 0.007±0.000 and 0.007±0.003 mg/l, respectively in the experimental group. The reference group exhibited As and Pb at 0.010±0.000 and 0.010±0.000 mg/l, respectively; whereas, Cd and Cr were not detected. As and Cd in the experimental group exceeded the water quality standard. The experimental group concentrations of As, Cd, Cr and Pb in sediment were 130.492±5.570, 120.466±14.576, 21.031±0.288 and 36.926±3.265 mg/kg, respectively. The reference group exhibited Cd, Cr and Pb at 0.390±0.288, 11.033±3.074 and 4.027±1.835 mg/kg, respectively, while As was not detected. As and Cd in the experimental group exceeded the soil quality standard. The experimental group concentrations of As, Cd, Cr and Pb in C. macrocephalus samples were 0.586±0.404, 2.314±2.369, 2.090±0.305 and 0.277±0.011 mg/kg, respectively. The reference group exhibited only Pb at 0.162±0.073 mg/kg. Cd and Cr in the experimental group exceeded the standard contamination in food. The diploid chromosomes of C. macrocephalus were 54 (2n=54). Chromosomal aberration in 50 kidney cells of three C. macrocephalus raised in heavy metals contaminated water and sediment from gold mine were found in 5 types including single chromatid gap (SCG), deletion (D), fragmentation (F), centric fragmentation (CF) and isochromatid gap (ISCG), which were detected at 4, 9, 1, 5 and 2 positions, respectively. The percentage of the cell numbers of chromosomal aberration was 9.33. The most of chromosomal aberration type in C. macrocephalus samples was D.